The history and frontiers of clinic electroencephalography technology - YU Miao; LIU Xiu‐yun; YUE Wei (Chinese Journal of Contemporary Neurology and Neurosurgery)
Electroencephalography (EEG), which can intuitively monitor and record the discharge activities of neuronal groups in the brain, is a crucial scientific and clinical diagnostic technique in the field of neuroscience. EEG has been developed and innovated for nearly a century, and it offers advantages of non ⁃ invasiveness, convenience, real ⁃ time, and continuity. The rapid advancement and multidisciplinary integration of computer technology and other imaging techniques has led to the application of EEG technology in a wide range of areas, including epilepsy, sleep disorders, and critical care. The purpose of this article is to enhance clinical comprehension and implementation of EEG technology by reviewing its development history, clinical applications, and future prospects.